The effect of the Smart Health Continuous Feedback For Elderly Exercise (SHe CoFFEE) program on mobility: a randomized controlled pilot study - Yi, Jungeun; Lee, Sunhee; Lee, Seon Heui (Frontiers in Public Health, 2024)
Objectives: This study determined the effectiveness of a comprehensive home-based online exercise program called "Smart Health Continuous Feedback for elderly exercise (SHe CoFFEE)" on mobility.Methods: Sixty community-dwelling seniors were randomized in a 1:1 ratio to intervention or control group.Intervention was an 8-week "SHe CoFFEE" program, featuring continuous feedback, self-monitoring, and fall prevention exercises. The primary outcome was mobility, measured at 8 weeks with the Timed Up and Go (TUG) test. Secondary outcomes included TUG at 4 weeks, 10m walking test, 30-second chair stand test, falls efficacy scale, activity-specific balance confidence, and Euro Quality of Life 5 Dimensions 5 Levels.Results: At 8 weeks, the intervention group showed improved TUG scores compared with the control group (MD= -1.87, 95% CI, -2.60 to -1.14; ηp 2 = 0.326) in the adjusted intention-to-treat analysis. The per-protocol analysis data showed similar results. All secondary outcomes apart from quality of life improved with intervention to a greater degree than in control.Conclusions: Smart healthcare and self-managed exercise programs may be viable for community-based health promotion and fall prevention in older adults unfamiliar with online technology.